Accelerated neurostimulation protocols for auditory hallucinations: a systematic review and meta-analysis - Hotz, Tremearne; Kosyakova, Natalia; Sharma, Manu (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the efficacy and characteristics of accelerated (more than once daily) protocols of repetitive transcranial magnetic stimulation (rTMS) and transcranial Electrical Stimulation (tES) in treating auditory hallucinations (AH) and other psychotic symptoms.Methods”We searched Pubmed” using relevant MeSH terms and keywords to identify relevant literature. Standard mean difference (SMD) and 95% confidence interval (CI) values were used to evaluate the effects of rTMS and tES.ResultsEighteen studies were included, eight which used rTMS and ten which used tES. AHs and positive psychotic symptoms (PPS) improved in all studies from before to after treatment (SMD = 0.64, 95%CI = 0.77 to 0.51). Superiority was seen in the groups using fMRI guidance and using cTBS. Thirteen studies used a sham group as a control, which collectively showed statistically significant improvement in AHs with a moderate effect size (SMD = 0.34, 95%CI - 0.50 to 0.18). However, these studies included a high level of heterogeneity as measured by Cochran’s Q and I2. Meta-analysis performed showed no consistent improvement of negative symptoms and did not differ significantly between the treatment and sham groups.ConclusionThere appears to be a therapeutic effect for accelerated neurostimulation protocols for AHs on par with non-accelerated approaches. These protocols take up less overall time and often provide less overall stimulus. This result needs to be confirmed by large-scale randomized controlled trials before this finding can be recommended in clinical practice.Systematic review registrationhttps://osf.io/69azy/, identifier 10.17605/OSF.IO/69AZY.